Teacher skills in classroom management at MI Muhammadiyah Gonilan - Desma Dzuriansyah; Almuntaqo Zainuddin (Inovasi Kurikulum)
Teacher skills in classroom management are needed so that the learning process in the classroom can run well and follow the goals desired by teachers and students. This research was conducted to determine and describe teachers' skills in classroom management at MI Muhammadiyah Gonilan using a qualitative descriptive approach and phenomenological model. The techniques used in collecting data are observation, interviews, and documentation. This research involved two resource persons: IVa and IVb homeroom teachers. The research results, among other things, show preparation for classroom management. Before entering class, the teacher prepares lesson plans and reference books and prepares students to participate in learning. Furthermore, in building positive relationships, the teacher is in charge of creating a comfortable atmosphere. Other research results relate to the implementation of classroom management. In classroom management, some factors support the implementation process. Several supporting factors include teaching aids, teachers' accompanying books or complete teaching materials, student books, and teachers and students arriving on time. Inhibiting factors are different children's concentration and different children's comprehension abilities.